Steering of Educational Processes in a Digital Medium Environment - Taekke, Jesper; Paulsen, Michael (Journal of Sociocybernetics, 2016)
This article is about challenges to steering and leadership of educational interaction in classrooms provided by the new medium environment that comes with digital media. In the new medium environment, the old way of steering what is going on in the classroom appears not to work any more since it was developed in the image of the industrial society and based on a closed classroom. Now with the digital media and wireless networks the classroom is opened and the old way of organizing teaching has become inadequate: The students are disturbed by the new media, instead of learning through them. Inspired by systems theory the paper sketches an outline of a more adequate way of teaching in the new medium environment – a teaching that can manage the new situation and use the new possibilities provided by the digital media. The paper builds on empirical findings from the action research project Socio Media Education (SME), which has worked with possibilities and problems in regard to the digital medium revolution’s disruption of the Danish upper secondary school (Author 1 & Author 2 2015a, b, 2014, 2013a, b, c, 2012).